(untitled) (International Journal of Communication Systems and Network Technologies, 2022)
The purpose of this work is to understand and unambiguously prove the best novel computational approach for microstrip antenna design. To design an improved model of microstrip antenna, which algorithm of artificial intelligence has been used for prediction.